Pengaruh Frekuensi Perdagangan Saham, Volume Perdagangan Saham, Kapitalisasi Pasar dan Jumlah Hari Perdagangan terhadap Return Saham (Studi pada Saham Perusahaan Dagang Eceran yang Terdaftar dalam Indeks Saham Syariah Indonesia Sebelum Sampai Sesudah Bul - taslim, ahmad; Wijayanto, Andhi (Universitas Negeri Semarang, 2016)
The purpose of this study is to determine how much effect of trading frequency, trading volume, market capitalization, and the sum of trading days on stock returnsbefore to after ramadhan. This research used secondary data from Indonesia Stock Exchange. Object study on Retail Trade Company Shares Listed In Indonesia Sharia Stock Index Before to Afterof Ramadan 2012-2014. The technique sampling used purposive sampling, methods of analysis using multiple linear regression analysis. The results of the analysis show: the trading frequency variable significant positive effect on stock returns, trading volume variable, market capitalization and trading day variables significant negative effect on stock returns.